2015
DOI: 10.1038/nature15548
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy mediates degradation of nuclear lamina

Abstract: Macroautophagy (hereafter referred to as autophagy) is a catabolic membrane trafficking process that degrades a variety of cellular constituents, and is associated with human diseases1–3. While extensive studies have focused on autophagic turnover of cytoplasmic materials, little is known regarding the role of autophagy in degrading nuclear components. Here we report that the autophagy machinery mediates degradation of nuclear lamina components in mammals. The autophagy protein LC3/Atg8, which is involved in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
547
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(576 citation statements)
references
References 39 publications
26
547
0
3
Order By: Relevance
“…A recent research demonstrates that the deacetylated nuclear LC3 is transported into the cytoplasm to carry out PE conjugation to pre-autophagic membranes by sequential interaction with Atg7 and Atg3 (34). Especially, nuclear lamina protein lamin B1 degradation is achieved by nucleus to cytoplasm transport degradation that delivers lamin B1 to the lysosome via LC3-lamin B1 interaction in the nucleus (31). The reduction in p90aDMA, p70aDMA and p34aDMA levels implicates the specificity and apparent affinity of aDMA for autophagy receptors (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent research demonstrates that the deacetylated nuclear LC3 is transported into the cytoplasm to carry out PE conjugation to pre-autophagic membranes by sequential interaction with Atg7 and Atg3 (34). Especially, nuclear lamina protein lamin B1 degradation is achieved by nucleus to cytoplasm transport degradation that delivers lamin B1 to the lysosome via LC3-lamin B1 interaction in the nucleus (31). The reduction in p90aDMA, p70aDMA and p34aDMA levels implicates the specificity and apparent affinity of aDMA for autophagy receptors (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, LC3 proteins play a key role in the selective recruitment of autophagic cargoes into autophagosomes, and serve as docking sites for adaptor proteins (12,31). Therefore, it is conceivable that proteins of aDMA including p90aDMA and p70aDMA as LC3 cargo substrates were translocated from the nucleus to the cytoplasm and tethered to the site of engulfing autophagosomes.…”
Section: Expression Of P90adma Is Specifically Enhanced By Il-2 Il-4mentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear membrane blebs containing lamin B1, induced by oncogenic stress, is also degraded by autophagy (Dou et al, 2015). In addition, it has been reported that autophagy is involved in the elimination of micronuclei (Rello-Varona et al, 2012), which are formed by mitotic abnormalities when exposed to genotoxic agents (Erenpreisa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In disease states, these include the actions of: (i) early-stage proinvasion metastasis drivers (12); (ii) novel macromolecular complexes (the epichaperome and HSP90/HSC70-associated nucleating sites) mediating tumor survival (13); (iii) autophagy-mediated degradation of the nuclear lamina that attenuate oncogene-induced senescence (14); (iv) recurrent double-strand DNA breaks/replication stress-associated fragile sites in neural stem/progenitor cells that predispose to specific neural cancers (15); (v) epigenetically mediated repression of genes promoting adult neuronal cell maintenance and de-repression of genes mediating alternative neural cell subtypes that orchestrate neurodegeneration (16); (vi) genome-wide HSF1 transcriptional effects that modulate promoter-proximal pause release, geneenhancer functions, and abrogation of neurodegenerative disease hallmarks (17); and (vii) enhanced developmental posttranslational modifications (DYRK1A protein kinase; Down's syndrome) normally predisposing to Alzheimer's disease that destabilize stress-responsive transcription factors (HIF2α) by inhibiting ID2-HIF2α feed-forward loops to abrogate glioma stem cell properties (inverse cancer comorbidity) (18). For physiological processes, these include the following: (i) rapid and selective nuclear export of gene transcripts encoding stress-responsive transcription factors without undergoing normal mRNA-mediated quality control (19); (ii) developmental stress signaling mediating cardinal maturational/maintenance cellular checkpoints [a differentiation checkpoint involving cross-talk between helix-loop-helix transcription factors and Hippo pathway signaling (20); a fitness checkpoint promoting organ integrity for cells exhibiting elevated levels of molecular/subcellular damage identified by alternatively spliced cell surface proteins and cell competition effects (21)]; and (iii) environmentally responsive neural codes for food abundance that modulate lifespan via stress resistance and metabolic reprogramming through the interplay of neuronal subtypes that encode food stores, metabolic states and stress responses (22).…”
mentioning
confidence: 99%